2017
DOI: 10.1038/ncomms15540
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rpn13-Rpn2 complex provides insights for Rpn13 and Uch37 as anticancer targets

Abstract: Proteasome–ubiquitin receptor hRpn13/Adrm1 binds and activates deubiquitinating enzyme Uch37/UCHL5 and is targeted by bis-benzylidine piperidone RA190, which restricts cancer growth in mice xenografts. Here, we solve the structure of hRpn13 with a segment of hRpn2 that serves as its proteasome docking site; a proline-rich C-terminal hRpn2 extension stretches across a narrow canyon of the ubiquitin-binding hRpn13 Pru domain blocking an RA190-binding surface. Biophysical analyses in combination with cell-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
126
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(144 citation statements)
references
References 70 publications
(133 reference statements)
14
126
2
Order By: Relevance
“…RA190, which can covalently bind to cysteine 88 of ADRM1 in the 19S regulatory particle of proteasome, inhibits proteasome function, resulting in higher-molecular weight polyubiquitylated protein accumulation [14,19]. In HCT116 cells, RA190 can also bind with UCH37, a deubiquitinating enzyme interacting with ADRM1, to suppress proteasome function [35]. Meanwhile, it was reported that KDT-11 could also suppress multiple myeloma by targeting ADRM1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…RA190, which can covalently bind to cysteine 88 of ADRM1 in the 19S regulatory particle of proteasome, inhibits proteasome function, resulting in higher-molecular weight polyubiquitylated protein accumulation [14,19]. In HCT116 cells, RA190 can also bind with UCH37, a deubiquitinating enzyme interacting with ADRM1, to suppress proteasome function [35]. Meanwhile, it was reported that KDT-11 could also suppress multiple myeloma by targeting ADRM1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…RP-associated Uch37 was found to progressively trim ubiquitin chains from the distal end, removing one ubiquitin moiety at a time [96,97]. Both proteasome-associated Uch37 and the isolated Uch37 catalytic domain have been shown to act on chains of varied linkage types [88,98,99], and RP-associated Uch37 has been reported to remove ubiquitin moieties from α-globin [96]. The efficiency of Uch37-mediated hydrolysis, however, seems strikingly low: whereas Usp14 acts on its preferred substrates within seconds [35], Uch37-mediated cleavage of Ub-chains takes much longer, with incubations of 30 minutes and even 8 hours [88,96,98,99].…”
Section: Substrate Specificitymentioning
confidence: 99%
“…Both proteasome-associated Uch37 and the isolated Uch37 catalytic domain have been shown to act on chains of varied linkage types [88,98,99], and RP-associated Uch37 has been reported to remove ubiquitin moieties from α-globin [96]. The efficiency of Uch37-mediated hydrolysis, however, seems strikingly low: whereas Usp14 acts on its preferred substrates within seconds [35], Uch37-mediated cleavage of Ub-chains takes much longer, with incubations of 30 minutes and even 8 hours [88,96,98,99]. It may be suggested that Uch37 acts slowly in order to provide the proteasome with ample time to degrade bona fide substrates [60], slowly deubiquitinating substrates that stall the proteasome until they are released.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…How might binding of polyubiquitin be communicated from the receptors to the Rpt motor proteins? Rpn13 is connected to the proteasome via attachment to a flexible extension at the C-terminus of Rpn2 (Figure 8A), and is fairly poorly resolved in cryoEM structures, suggesting that a range of conformations may be possible 58 . Ubiquitin occupancy may then be communicated to the ring of Rpt motor proteins via these different conformations.…”
Section: Discussionmentioning
confidence: 99%